The improvement of physical and mechanical properties of cement decorative ornaments by adding wasted paper - Hongsri, Korpong; Somboon, Kwanjai (Bulletin of Applied Sciences, 2016)
The aim of this project was to improve physical and mechanical properties of decorative ornaments made from cement with the ratio of cement: gypsum : sand : water equaled to 1:0.25: 0.25: 4 by adding different types of wasted paper, which were printing paper, newspaper paper, cardboard paper and mix wasted paper with the ratio of cement : gypsum : sand : water : wasted paper equaled to 1:0.25: 0.25: 4:0.1 respectively and to discover the most appropriated type of the wasted paper to be used to create a mix cement-paper decorative ornaments. The study found that by adding wasted paper into the mixture of cement, the density and modulus of rupture of the cement decorative ornament decreased, whereas water absorption, thickness swelling and modulus of elasticity of the cement decorative ornament increased. This proved that by adding wasted paper into the mixture of cement, the cement-paper mixture was more suitable to make decorative ornaments as the products were lighter and had more flexibility. The cardboard paper was the most suitable wasted paper to be used as it provided the best physical and mechanical properties improvements which were the density of 2,215 gcm-3, the water absorption of 44.1 %, the thickness swelling of 1.56 %, the modulus of rupture of 1.384 megapascal and modulus of elasticity of 2,424 megapascal. It can be concluded that where the cement-paper mixture was used to make decorative ornament, it was found that it can be used to make more variety of decorative ornaments because of its lightness, easier to cut and shaped. Using wasted paper also helped reducing the cost of production.